2017
DOI: 10.1371/journal.pone.0175160
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient enrichment is associated with altered nectar and pollen chemical composition in Succisa pratensis Moench and increased larval mortality of its pollinator Bombus terrestris L.

Abstract: Pollinators are declining worldwide and possible underlying causes include disease, invasive pest species and large scale land use changes resulting in habitat loss and degradation. One particular cause of habitat degradation is the increased inflow of nutrients due to anthropogenic combustion processes and large scale application of agricultural fertilizers. This nutrient pollution has been shown to affect pollinators through the loss of nectar and pollen-providing plant species. However, it may also affect p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 53 publications
(79 reference statements)
1
59
1
Order By: Relevance
“…Ceulemans, Hulsmans, Van den Ende, et al. () also found increased asparagine in the pollen of Succisa pratensis , an N‐sensitive species. Interestingly, Gardener and Gillman () observed that soil enrichment increased production of glutamine and proline and decreased production of GABA (Gamma‐aminobutyric acid) in the nectar of Agrostemma githago .…”
Section: Impacts On Higher Trophic Levelsmentioning
confidence: 86%
See 3 more Smart Citations
“…Ceulemans, Hulsmans, Van den Ende, et al. () also found increased asparagine in the pollen of Succisa pratensis , an N‐sensitive species. Interestingly, Gardener and Gillman () observed that soil enrichment increased production of glutamine and proline and decreased production of GABA (Gamma‐aminobutyric acid) in the nectar of Agrostemma githago .…”
Section: Impacts On Higher Trophic Levelsmentioning
confidence: 86%
“…In contrast, increased soil N was found to reduce the overall nectar‐sugar reward to pollinators in a lepidoptera‐pollinated orchid, Gymnadenia conopsea (Gijbels, Van den Ende, & Honnay, ). Even if the total sugar reward of nectar or pollen is unaffected, the composition of sugars can be altered by N addition (Ceulemans, Hulsmans, Van den Ende, & Honnay, ; Hoover et al., ). However, this is also species‐specific, with other plant species not showing a change in sugar composition (Gijbels, Ceulemans, Van den Ende, & Honnay, ).…”
Section: Impacts On Higher Trophic Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, excessive soil nutrients can decrease amino acid concentrations in pollen, with consequences for bumble bee larval survival (Ceulemans et al 2017). For example, excessive soil nutrients can decrease amino acid concentrations in pollen, with consequences for bumble bee larval survival (Ceulemans et al 2017).…”
Section: Amf and Nutrients Affect Bee Pathogens Via Changes In Floralmentioning
confidence: 99%